P073 Compartmentalised human gut immunity: studies of innate and adaptive lymphocyte distribution in the epithelium, lamina propria and GALT of healthy gut mucosa by flow cytometry. (15th January 2020) - Carrasco Garcia, A; Rao, A; Kokkinou, E; Haapaniemi, S; Lindforss, U; Winberg, M E; Casado-Bedmar, M; Fenton, T; Jørgensen, P; Nordenvall, C; Agace, W; Keita, Å V; et al.
Abstract: Background: The human gut mucosal immune system is compartmentalised in distinct and specialised immune niches. The epithelium and the lamina propria have been proposed as effector sites, while gut-associated lymphoid tissues (GALTs) constitute inductive immune niches. The major mucosal GALTs are the Peyer's patches in the ileum and the colonic isolated lymphoid follicles (ILFs), scattered in the submucosa of the colon. The majority of studies of human gut immune function in health and disease have analysed unfractionated mucosal tissue samples. Hence, in contrast to mice, little is known about compartmentalised immune cell specialisation in the human gut. The aim of this study was to use novel dissection methods to analyse separate human gut immune niches. Methods: Macroscopically healthy margins from colorectal cancer colectomies were obtained at a minimum distance of 10 cm from the tumour border. After faeces, mucus, fat and muscle removal, Peyer's patches were identified and dissected using a stereomicroscope (based on Keita et al., Lab Invest, 2006). Colonic mucosa and submucosa (containing ILFs) fractions were mechanically separated by forceps (based on the method developed by Fenton et al., Immunity, under revision). Isolation of epithelial and lamina propria fractions from the mucosal compartment was performed by calcium chelation (DTT and EDTA) and enzymatic digestion (Collagenase II and DNAse), respectively. Cell suspensions from each fraction were analysed by flow cytometry (BD LSR-Fortessa and BD FACSymphony). Results: As expected, mucosal GALTs were characterised by an enrichment of germinal centre B cells (CD19 + CD20 + CD38 + ), lymphoid tissue-like innate lymphoid cells (Lin−CD127 + CD117 + Nrp1 + ) and a higher CD4 + /CD8 + T-cell ratio vs. mucosa, whereas the mucosal fraction was enriched for plasma cells (CD19 + CD20−CD38 high ) and distinguished by a decreased CD4 + /CD8 + T-cell ratio as compared with the GALT in both ileum and colon. CD19 + /CD3 + ratios were only higher in Peyer's patches but not in colonic submucosa enriched with ILFs, possibly due to the smaller size of the B-cell follicles in the latter. The intraepithelial compartment lacked B cells and contained more γδ-T cells as compared with the GALT and lamina propria. Conclusion: We have used novel dissection methods in human intestinal tissues that reveal a compartmentalised immune cell specialisation that is in line with what has previously been described in mice. The method will allow for future deeper analysis of the human gut immune niches in health and disease, such as in inflammatory bowel disease.